2017
DOI: 10.1002/anie.201704046
|View full text |Cite
|
Sign up to set email alerts
|

Strain Stiffening Hydrogels through Self‐Assembly and Covalent Fixation of Semi‐Flexible Fibers

Abstract: Biomimetic, strain‐stiffening materials are reported, made through self‐assembly and covalent fixation of small building blocks to form fibrous hydrogels that are able to stiffen by an order of magnitude in response to applied stress. The gels consist of semi‐flexible rodlike micelles of bisurea bolaamphiphiles with oligo(ethylene oxide) (EO) outer blocks and a polydiacetylene (PDA) backbone. The micelles are fibers, composed of 9–10 ribbons. A gelation method based on Cu‐catalyzed azide–alkyne cycloaddition (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
76
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 26 publications
2
76
0
1
Order By: Relevance
“…Moreover, the critical stress of the stiffening σ c showed a linear dependence of c , that is, σ c ≈ c 1.8 , which enables the rescaling of the K ′ versus σ curves to G 0 and σ c , respectively. We found that all the rescaled curves corresponding to different c overlapped at a single master curve, indicating that all gel samples undergo a common stiffening mechanism …”
Section: Figuresupporting
confidence: 83%
See 3 more Smart Citations
“…Moreover, the critical stress of the stiffening σ c showed a linear dependence of c , that is, σ c ≈ c 1.8 , which enables the rescaling of the K ′ versus σ curves to G 0 and σ c , respectively. We found that all the rescaled curves corresponding to different c overlapped at a single master curve, indicating that all gel samples undergo a common stiffening mechanism …”
Section: Figuresupporting
confidence: 83%
“…Kouwer and colleagues presented the first example of synthetic strain‐stiffening hydrogels that are formed by the entanglement of semi‐flexible polyisocyanopeptides (PICs) bundles, closely mimicking the characteristic mechanical properties of biological intermediate filaments . The other example was described very recently by Sijbesma . In their work, strain‐stiffening hydrogels are prepared by covalently crosslinking of semi‐flexible rod‐like micelles that are formed through self‐assembly and covalent fixation of oligo(ethylene oxide) grafted bisurea bolaamphiphiles.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Several strategies have been used to recapitulate such mechanochemical behavior in materials. For instance, strain‐stiffening synthetic hydrogels have been engineered through the synthesis of polymers with semiflexible backbones, which organize into a mesh‐like architecture and mechanical loading induces polymer extension and packing . Additionally, mechanochemical polymers have been designed with latent mechanophores that are activated under destructive shear forces and undergo crosslinking to increase bond density to higher levels than before bond breakage (i.e., strengthening) or create mechanoradicals in response to bond scission, that promote growth of polymer networks and increased crosslinking (i.e., toughening) .…”
mentioning
confidence: 99%